Lexicographical exploration of Québec French sources. (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
This article aims to identify different sources of Quebec French based on eight words specific to the lexicon or culture of Quebec (use now outdated in France, borrowing from an indigenous language, borrowings from English, neologisms, etc.). This exploration through words allows us to retrace the journey of encounters between different peoples with whom the French speakers of Quebec have been in contact throughout their history. The present study also retraces the description of Quebec words, over several centuries, in certain dictionaries made in France and puts these visions in dialogue with real usage and with certain dictionaries which constitute important milestones in the lexicography of Quebec over the last 150 years.
Keywords: Quebec French; maringouin; orignal; ouaouaron; borrowings; anglicisms